The interplay of syntax and form in sentence production: a cross-linguistic study of form effects on agreement. - Franck J; Vigliocco G; Antón-Méndez I; Collina S; Frauenfelder UH (Language & Cognitive Processes, 2008)
We report four cross-linguistic experiments (in Spanish, Italian and French) testing the influence of morphophonological gender marking in the subject noun phrase on the production of gender agreement. Agreement errors are elicited using a methodology in which participants are required to complete, with a predicative adjective, a sentence preamble. Results confirm a role for morphophonological gender marking in agreement. More precisely, we show that this role varies with two factors of different nature. The first factor is structural and has to do with the position of the marker in the noun phrase (article vs. noun). The second factor is distributional and has to do with the validity of the marker in the language. A model of agreement production is proposed in which two functionally distinct processes are identified: Feature selection, the locus of the morphophonological influences, and Feature copy, operating under strict syntactic guidance.